O princípio da vedação ao retrocesso social e o papel dos poderes públicos na efetivação dos direitos fundamentais sociais - Andrade, Júlio Thalles de Oliveira (2013)
The purpose of this dissertation is to analyze the role of Public Powers in the enforcement of fundamental social rights, according to the principle of prohibition to social regression. The Federal Constitution of Brazil, situated in a position normative hierarchical superior, disciplines the legal and political process of the country, determining how Public Powers (Legislative, Executive and Judiciary) should act to enforce fundamental rights (social). Thus, features a cast of fundamental rights that aim to ensure social justice, highlighting the concern to ensure social values aimed at reducing social inequalities. The will of the state should be prevented by controlling the constitutionality of measures which restrict fundamental social rights, assuming the principle of human dignity, pillar of Social and Democratic State of Right, a dual role in the brazilian legal system, acting as the presupposition of jurisdictional control of the constitutionality of restrictive acts and as supervisory of omission or insufficient action of the State in the fulfillment of their fundamental duties. The constitutional determinations remove from the legislator the option to create or not the law that prints effectiveness to the social rights, as well as from the Executive the option of to execute or not rules directed at realization of the constitutional parameters, and Judiciary to behave or not in accordance with the Constitution, being given to the Powers only the arbitrariness of "how" to do, so that all functions performed by public actors to use the Constitution as a repository of the foundational values of the collectivity. Any situation that does not conform the principle of proportionality in relation to the enforcement of fundamental rights, especially the social, represents an unacceptable social regression unconstitutional. The constitutional rules and principles postulated by the realization of the rights, freedoms and guarantees of the human person, acting the principle of prohibition to social regression to regulate a concrete situation, whenever it is intended to change, reducing or deleting, the content of a social right. This paper of limit of state action serves to provide to the society legal security and protection of trust, ensuring the core of every social right. This should be effected to be sheltered the existential minimum, as a guarantee of the inviolability of human life, respecting the constitutional will, not falling into social regression